2016
DOI: 10.5194/isprs-archives-xlii-4-w1-25-2016
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Coastline Changes to Local Community’s Social-Economic

Abstract: ABSTRACT:The coastal area is absolutely essential for the purposes of resident, recreation, tourism, fisheries and agriculture as a source of socioeconomic development of local community. Some of the activities will affect the coastline changes. Coastline changes may occur due to two main factors include natural factors and also by the factor of human activities in coastal areas. Sea level rise, erosion and sedimentation are among the factors that can contribute to the changes in the coastline naturally, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 4 publications
1
18
0
Order By: Relevance
“…Pussella et al (2015) agreed that approximately 41% of the world's inhabitants are concentrated in the coastal zone, which can be defined as the area within 100 km of the coastline. Hassan and Rahmat (2016) posit that coastal regions are characterized by multi-functional developments such as recreation, residential, tourism, industry, agriculture, aquaculture and others. Furthermore, the population migration motion is increasingly focussed on the coastal regions which affect economic development.…”
Section: Buildings Along Lagos Coastlinementioning
confidence: 99%
See 1 more Smart Citation
“…Pussella et al (2015) agreed that approximately 41% of the world's inhabitants are concentrated in the coastal zone, which can be defined as the area within 100 km of the coastline. Hassan and Rahmat (2016) posit that coastal regions are characterized by multi-functional developments such as recreation, residential, tourism, industry, agriculture, aquaculture and others. Furthermore, the population migration motion is increasingly focussed on the coastal regions which affect economic development.…”
Section: Buildings Along Lagos Coastlinementioning
confidence: 99%
“…These buildings are however vulnerable to a high rate of defects as a result of the extreme conditions of the climate around the coastal region (Kumar et al, 2010), Mukhopadhyay et al (2012) identified several climatic conditions that pose a danger to the lives and assets within the coastal zone to include: floods, debris flows, mudflows, cyclones, storm surges, snow avalanches, sand or dust storms, surface collapse and liquefaction. Hassan and Rahmat (2016) also identified the climatic circumstances that buildings along the coastal regions are exposed to include: waves and currents, storms, landslides, sea-level rise, saltwater intrusion, floods and droughts and greater intensity of heatwaves. Michalou (2015) defined deterioration as a natural process that results in materials responding to altering circumstances and can alter change the physical, chemical and mechanical characteristics of the materials either slowly or rapidly.…”
Section: Buildings Along Lagos Coastlinementioning
confidence: 99%
“…In Peninsular Malaysia, the intrusion of seawater has caused damage to large areas of agricultural land and properties; public facilities and coastal roads have been destroyed and caused transportation delay. The intrusion of seawater has also caused damage to beaches and this have had adverse impact on the tourism industry (Ehsan et al, 2019;Ghazali, 2006;Hassan & Rahmat, 2016;Mohd et al, 2019;Rameli & Jaafar, 2018;Razak et al, 2018;Selamat et al, 2017;Stanley & Lewis, 2009, 2009.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Information such as aerial photographs, topographic, bathymetric surveys, beach profiles, and historical maps can be used to qualitatively and quantitatively assessment the spatial and temporal changes in coastal areas (Mohd Azharn et al, 2018;Selamat et al, 2017). The latest GIS and remote sensing technologies are capable of extracting and detecting shoreline changes from satellite images (Asmawi & Ibrahim, 2013;Camara et al, 2019;Din Hashmi & Ahmad, 2018;Hassan & Rahmat, 2016;Mohammad et al, 2007;Mohd Azharn et al, 2018;Nassar et al, 2019;Pantanahiran, 2019;Selamat et al, 2017). According to Pantanahiran (2019), in order to calculate erosion and deposition in coastal areas, GIS requires inputs such as aerial photographs and satellite images.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation